Download presentation

Presentation is loading. Please wait.

Published byImogen Powell Modified over 4 years ago

1
Objective 24 Solve equations, combine like terms ©2002 by R. Villar All Rights Reserved

2
Solve equations, combine like terms It is usually easier to simplify an expression prior to solving an equation... In these examples, we will combine like terms first, and then solve the resulting equation... Example –6x – 8x = 7 Combine the like terms –6x and –8x first... –14x = 7 Now, solve... –14 –14 x = – 1 2 You can check the original problem... –6(–1/2) – 8(–1/2) = 7 3 + 4 = 7 √

3
Example:–4x + 23 + 6x + 23 = – 2 Combine the like terms first…–4x with +6x and +23 with +23 2x + 46 = – 2 – 46 –46 2x = –48 2 2 x = – 24 Check –4(–24) + 23 + 6(–24) + 23 = –2 96 + 23 – 144 + 23 = – 2 √

4
Let’s look at an example that has variables on both sides of the equation... Example:5x + 6 = 2x – 3 The strategy to solve this type of problem is to get variables on one side, and numbers (constants) on the other side. variable side number side 5x + 6 = 2x – 3 – 6 – 6 5x = 2x – 9 –2x –2x 3x = – 9 x = – 3

Similar presentations

© 2019 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google